Ничего кроме правды: Нюрнбергский процесс: воспоминания переводчика / Татьяна Ступникова - Ступникова Татьяна Сергеевна (Возвращение, 2003)
Цена: / Сис.шифр: 67.91 / Авт.знак: С88 / ГРНТИ: 10.87 / ББК: 67.919